Tourism management : A modern Synthesis - Page, Stephen, 1963- (United Kingdom Cengage, 2014)
'Tourism Management' is a complete synthesis of tourism, from its beginnings, through to the major impacts it has on today's global community, the environment and economy.
Previous editions had subtitle: Manageing for change.
Previous ed.: 2009.
Includes bibliographical references and index.
Keywords: Tourism -- Textbooks; Tourism -- Management -- Textbooks